Open Lab Starter Kit Small Laser V2–an open source Fab lab produced laser cutter - Daniele Ingrassia; Gaia Di Martino; J.C. Mariscal-Melgar; Mohammed Omer; Liane Sayuri Honda; Luisa Lange; Marc Kohlen; Manuel Moritz; Tobias Redlich (HardwareX)
The rise of Open Source manufacturing ecosystems is a multifaceted phenomenon, fueled by the proliferation of digital fabrication technologies, the collaborative spirit of the Open Source movement, and the creation of spaces like hackerspaces, and fab-labs. Part of the efforts is the Open Lab Starter Kit (OLSK), a set of machines designed to lower the barriers to entry for everyone. The OLSK Small Laser V2, an integral component of the OLSK, represents the second phase of design and prototyping within the scope of an Open Source Laser Cutter initiative. Being reproducibility and accessibility central goal of the OLSK, great attention was given not only to the design of the hardware, but also to the development of comprehensive documentation. The documentation, encompassing repositories and assembly manuals, assumes a pivotal role within the project framework, aiming to facilitate swift reproduction and user-friendly accessibility. Functionally, the OLSK Small Laser V2 is comparable with mainstream off-the-shelf laser cutters, demonstrating proficient cutting capabilities across commonly processed materials compatible with a 40 W CO2 laser cutter, such as plywood, acrylics and Medium-Density Fiberboard (MFD), with a cutting area of 400 mm x 600 mm.